Experimental analysis of stereotypy with applications of nonparametric statistical tests for alternating treatments designs. - Lloyd, Blair P.; Finley, Crystal I.; Weaver, Emily S. (Developmental Neurorehabilitation, 2018)
Introduction: Stereotypy is common in individuals with developmental disabilities and may become disruptive in the context of instruction. Purpose: The purpose of this study was to embed brief experimental analyses in the context of reading instruction to evaluate effects of antecedent and consequent variables on latencies to and durations of stereotypy. Method: We trained a reading instructor to implement a trial-based functional analysis and a subsequent antecedent analysis of stimulus features for an adolescent with autism in a reading clinic. We used alternating treatments designs with applications of nonparametric statistical analyses to control Type I error rates. Results: Results of the experimental analyses suggested stereotypy was maintained by non-social reinforcement and informed the extent to which features of academic materials influenced levels of stereotypy. Results of nonparametric statistical analyses were consistent with conclusions based on visual analysis. Conclusion: Brief experimental analyses may be embedded in academic instruction to inform the stimulus conditions that influence stereotypy.